Priorities in Planning (Food, Education, Housing) - Planning Commission (Planning Commission, 1946)
Until the release of Political leaders, in June 1945, the National Planning Committee was unable to function with the regularity and expedition originally intended, as its Chairman, Pandit Jawaharlal Nehru, was inaccessible practically all through 1940-45. Informal consultations were held at the very first opportunity, after his release, in June 1945 ; and in the September following, an informal meeting of the Committee and some of the Chairmen and Secretaries of Sub-Committees was held in Bombay.
Priorities in Planning
The National Planning Committee